Immunogenicity and safety of co-administration with the Sabin-strain-based inactivated poliovirus vaccine (vero cell) and the diphtheria-tetanus-acellular pertussis vaccine in eligible children in China: a randomized, controlled, multicenter, non-inferiority trial - Liu, Xiaoyu; Han, Shasha; Chen, Xiao; Sun, Li; Wang, Ruize; Shi, Xuanwen; Guo, Yu; Wang, Hui; Chen, Haiping; Chang, Shaoying; Xu, Xiaomeng; Zhang, Chao; et al. (Frontiers in Immunology, 2025)
ObjectiveIn developing countries, combined vaccine availability remains limited due to economic constraints, healthcare infrastructure, and supply chain challenges. While some imported combined vaccines are available in China, their accessibility is restricted. Co-administration of individual vaccines presents a viable alternative. This study evaluates the immunogenicity and safety of simultaneous sIPV and DTaP administration to support vaccination policies and improve immunization rates.MethodsIn this randomized, controlled, open-label, multicenter non-inferiority trial, 702 healthy 3-month-old infants from Shaanxi, Shanxi, and Hebei provinces were enrolled and assigned to three groups: Group 1 (sIPV + DTaP co-administration), Group 2 (sIPV alone), and Group 3 (DTaP alone). Vaccines were administered on a 3-4-5-month schedule. Serum samples were collected pre-vaccination and 30 days post-vaccination to assess antibody responses. Adverse events (AEs) were monitored for safety evaluation.ResultsAmong 671 infants completing the study (642 per protocol), co-administration (Group 1) demonstrated non-inferior immunogenicity compared to separate administration. Seroconversion rates and geometric mean titers (GMTs) for poliovirus types 1,2 and 3 were comparable between Groups 1 and 2. For anti-PT, FHA, D, T, Group 1 showed non-inferiority to Group 3 in seroconversion. However, anti-PT and anti-FHA geometric mean concentrations (GMCs) were lower (Group 1:anti-PT 31.06 [95% CI: 28.56–33.77], anti-FHA 29.40 [27.68–31.24]; Group 3: anti-PT 39.32 [36.25–42.65], anti-FHA 33.06 [31.01–35.24]). No significant differences were observed in anti-D and anti-T GMCs. AE rates were similar across groups, with local reactions (e.g., induration) more frequent in Group 1 (6.84%) than in Group 2 (0.85%). Systemic AEs (primarily grade 1–2 fever) did not differ significantly.ConclusionCo-administration of sIPV and DTaP is immunogenically non-inferior to separate administration and demonstrates comparable safety. This strategy is feasible and may support simplified immunization schedules in China.Clinical trial registrationClinicalTrials.gov, identifier NCT04053010.